2020
DOI: 10.1002/eat.23320
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone is associated with dysregulated eating symptoms in young adult men

Abstract: Objective Extant animal and human data indicate that natural variation in circulating levels of testosterone may contribute to differential risk for dysregulated eating among males. Indeed, testosterone ablation in postpubertal male rodents results in stimulatory effects on sweet‐taste preferences, and lower levels of circulating testosterone in adolescent boys have been found to predict dysregulated eating symptoms during mid‐to‐late puberty. Nonetheless, no prior study has examined whether lower testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This “stress acceleration hypothesis” is consistent with our findings of earlier activation of genetic influences in boys experiencing disadvantage. While stress is associated with increased disordered eating (Gadalla, 2009; Mitchell et al, 2016) and androgens are generally protective against disordered eating in men and boys (Culbert et al, 2014, 2020), no studies have yet examined how androgens and stress may interact to impact ED risk. Additional longitudinal research is needed to identify how the stress accompanying disadvantage may interact with androgens during development to impact gene expression and neural development in boys.…”
Section: Discussionmentioning
confidence: 99%
“…This “stress acceleration hypothesis” is consistent with our findings of earlier activation of genetic influences in boys experiencing disadvantage. While stress is associated with increased disordered eating (Gadalla, 2009; Mitchell et al, 2016) and androgens are generally protective against disordered eating in men and boys (Culbert et al, 2014, 2020), no studies have yet examined how androgens and stress may interact to impact ED risk. Additional longitudinal research is needed to identify how the stress accompanying disadvantage may interact with androgens during development to impact gene expression and neural development in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, androgens do not induce eating disorders, such as anorexia nervosa or bulimia nervosa, in contrast to estrogens, which display such effects, hence the rare occurrence of eating disorders in males [ 29 ]. However, there are data indicating that lower testosterone in men is associated significantly with eating disorders regardless of depressive symptoms, body mass index, and age [ 30 ].…”
Section: The Psychological Aspect Of Obesity and The Influence Of Cor...mentioning
confidence: 99%
“…Several explanations for inconsistent findings in humans are possible. Elevated prenatal/perinatal testosterone could have the strongest impact on later binge eating when testosterone is also relatively high in adolescence/adulthood [ 53 , 54 ], as typically occurs for men, but not women. However, the Culbert et al [ 18 ] study discussed above observed protective effects of perinatal testosterone on BEP phenotypes in female rats even without administration of testosterone in adolescence/adulthood, suggesting that the protective effects of testosterone early in life do not fully depend on later testosterone exposure.…”
Section: The Prenatal/perinatal Period: a Key Stage For Brain Organiz...mentioning
confidence: 99%
“…By adulthood, organization of neural circuits by gonadal hormones appears mostly complete, and effects are more activational in nature [ 32 ]. Androgens continue to be protective in males, with higher testosterone levels associated with less binge eating in young adult men [ 53 ]. Interestingly, testosterone may have the opposite effect in adult women [ 70 ].…”
Section: Reproductive Age: Dynamic Activational Hormone Effectsmentioning
confidence: 99%